Security Culture and its Self-Assessment as Supplementary Tools for Nuclear Security Training - Igor Khripunov; Sara Z. Kutchesfahani; Khairul - Khairul - (International Journal of Nuclear Security, 2016)
Security Culture and its Self-Assessment as Supplementary Tools for Nuclear Security Training Igor Khripunov, PhD Center for International Trade and Security, University of Georgia (USA) Sara Z. Kutchesfahani, PhD Center for International Trade and Security, University of Georgia (USA) Khairul Khairul National Nuclear Energy Agency of Indonesia (BATAN) Abstract Nuclear security culture – an emerging and widely recognized practice – serves as a means to support and enhance nuclear security. In fact, many International Atomic Energy Agency (IAEA) publications and the Nuclear Security Summits have highlighted the vital role of nuclear security culture and raised its status to the same level as physical protection and material accountancy. Consequently, there is a great need to include the concept of nuclear security culture and its self-assessment methodology in existing nuclear security education and training programs as a cross-cutting topic and as a means to improve the efficiency of the currently applied learning methods. This paper outlines the importance of including training modules on nuclear security culture and its self-assessment as a way in which to improve and complement existing nuclear security education and training programs.
Keywords: Nuclear Security Culture; Human Factors; Nuclear Security